La digitalización, como estrategia táctica focal, dentro del aprendizaje colaborativo; caso de estudio: La Matemática (en inglés) - Basantes-Valverde, Williams; Astudillo-Condo, Daysi; Tixi-Gallegos, Katherine (Educación y sociedad, 2025)
Initially, it is necessary to infer the way in which teachers contribute knowledge to the smart classroom. To this end, the objective of this study, as the basis of the educational environment and within digital pedagogy, manifests the didactic ability as a technicality of instruction. However, this research is based on the prism methodology and the bibliography admits technology as a bastion of ubiquity in resulting edges. Thus, digital connection is considered as the driving force of learning and its competencies are focus strategies. As much as these serve as educational tools in the digital age, they promote knowledge and expose, as derivation, cognitive thinking; safeguarding, in the classroom universe, competencies as a standard and establishing digitalization as the foundation of learning. Finally, in their search, technological instruments and computational certainty supported a practical assumption; case of Mathematics in an Ecuadorian University.